Pemberian Senam Ergonomik Berbasis Spiritual pada Lansia dengan Prediksi Arthritis Gout di wilayah kerja Puskesmas Sokaraja I - Triana Ayu Anggraeni; Ikhsan Mujahid (Jurnal Keperawatan Muhammadiyah, 2020)
ABSTRACT Background: Gout which is commonly known as athritis gout is a disease caused by the accumulation of monosodium uric crystals in the body. Athritis gout is a degenerative disease that attacks the joints and is often experienced by the elderly. Athritis gout can be intervened with non-pharmacological therapy, one of which is ergonomic gym. Ergonomic gym is a muscle movement that is combined with breathing techniques.Objective: To figure out the influence of giving spiritual-based ergonomic gym to the elderly with prediction of arthritis gout in the working area of Public Health Care Center of Sokaraja I.Method: A quantitative method was used in this study. The quasi- experimental pre-test and post-test nonequivalent control group design was used as research design. The samples were elderly people aged 45-59 years in Integrated Health Service Post (Posyandu) Karangnanas in the working area of Public Health Care Center of Sokaraja I. There were 42 respondents which were collected by using the consecutive sampling method in December 2019. The research instruments were in the form of respondent demographic data, pre-posttest observation sheets and a tool to check uric acid levels.Results: The average difference in measurement of uric acid levels (pre-posttest) in the treatment group was 0.5619, while in the control group, it was 0.3000. T-Test Independent results on the difference in the pre-posttest results of the treatment group and the control group obtained p-value of 0.002 or p <0.05. It meant that there were significant differences in the decrease of uric acid levels between the treatment group and the control group.Conclusion: There is a difference in the decrease of uric acid levels in the treatment group and the control group. The result shows the influence of giving spiritual-based ergonomic gym for decreasing uric acid levels in the elderly with arthritis gout prediction.Keywords: Arthritis Gout, elderly, spiritual based ergonomic gym